(untitled) (Bangladesh Journal of Urology, 2026)
Introduction: Renal Cell Carcinoma (RCC) with Inferior Vena Cava (IVC) involvement is rare, occurring in 4%–10% of cases with RCC. The IVC tumour removal is associated with a high mortality. There is no large series reporting such cases from Sri Lanka. This study is on a series of patients with RCC and IVC tumour thrombus, who underwent successful venous tumour removal. Methods: This is a descriptive retrospective study of consecutive patients undergoing surgery over four years. The level of extension of RCC tumour thrombus was categorised into level I (renal vein), level II (infrahepatic IVC), level III (retro hepatic) and level IV (suprahepatic). Results: 24 were included. 16 (66.7%) were males. Mean age was 60.7 years (37-79). 64.3% presented with a palpable mass while17.9% had haematuria. Three (12.5%) had lung metastasis. There were three (12.5%) were level I, six (25.0%) level II, 11 (45.8%) level III and four (16.7%) level IV tumours. The commonest histological type was clear cell carcinoma (85.0%). The mean follow up was 11.2 months (0.2 to 50.7). The one month and one year survival was 96.0 % and 72.0%. Discussion and Conclusions: This is the largest case series of RCC with venous tumour thrombus extension from Sri Lanka. The one month and one year survival was 96.0 % and 72.0%. This is comparable to other such series. However a larger study with longer follow-up is required before drawing further conclusions. Bangladesh J. Urol. 2025; 28(2): 100-104